Amplification of fluorescent-labelled microsatellite markers in olives by a novel, economic method - Dunja BANDELJ; Jernej JAKŠE; Branka JAVORNIK (Acta Agriculturae Slovenica)
A novel method for the economic fluorescent labelling of PCR products and its features are described. To investigate the efficiency of the method for amplification of olive microsatellite markers, PCR conditions of three loci were optimised. The results showed that the method can be successfully applied in genotyping studies of olive varieties.